Linking research with extension and implications for farming systems in Malaysia - Mohd Yassin, Sulaiman (1985)
The paper outlines the concept of relevant research, effective extension work and the organization of clients as pre-requisites for a sound system for increasing farmer productivity. The current practical problems accruing from the related processes of technology generation, technology transfer and technology application are further clarified and illustrated by available local examples. The prevailing demands on a rethinking and adjustment and more effective extension-research linkages with the farming system because of recent policy changes and the outlook for farming improvement are further analyzed and submitted for discussion.